Revisiting the Meissen Declaration after 30 years - Chapman, Mark D.; Nüssel, Friederike; Grebe, Matthias (Evangelische Verlagsanstalt, 2020)
The Theological Conference between the Church of England and the Evangelical Church in Germany is a key component of the Meissen Declaration, which was adopted 30 years ago and to which the churches have committed themselves in order »to resolve the outstanding differences between the participating churches«. To highlight the importance of the relations in a time of political uncertainty, the 2019's conference was dedicated to »Revisiting the Meissen Declaration after 30 years«. Discussion focused on the interchangeability of ministries, with reference to the understanding of this by the church and episcopate. The papers focus on significant ecclesial and historical/theological developments. They attend to questions about the church and the episcopate with regard to ecclesial identity and in light of contemporary European ecumenical developments as well as sociological changes over the last three decades. With papers by Mark Chapman, Jonathan Gibbs, Matthias Grebe, Stephen Hampton, Ralf Meister, Friederike Nüssel, Bernd Oberdorfer, Rowena Pailing, Hilke Rebenstorf, Andrea Russell, Christof Theilemann, Martin Wallraff and Michael Weinrich. [Relecture des Meissen-Abkommens nach 30 Jahren] Die Theologische Konferenz der Church of England und der EKD ist ein zentraler Bestandteil der Meissener Erklärung, die vor dreißig Jahren verabschiedet wurde und in der sich beide Kirchen verpflichteten, »an der Überwindung der bestehenden Unterschiede zu arbeiten«. Im Bewusstsein der Bedeutung der gewachsenen Beziehungen in einer Zeit politischer Unsicherheit wurde die Konferenz von 2019 der »Relecture des Meissen-Abkommens nach 30 Jahren« gewidmet. Im Zentrum stand die Frage nach der Austauschbarkeit von Ämtern im Lichte des Verständnisses von Kirche und Bischofsamt. Die Beiträge behandeln kirchen- und theologiehistorische Entwicklungen und erörtern Fragen des Kirchen- und Episkopatsverständnisses in Rücksicht auf kirchliche Identität und unter Beachtung aktueller ökumenischer Entwicklungen in Europa und den soziologischen Veränderungen beider Kirchen in den letzten dreißig Jahren.
Online resource; title from title screen (viewed May 11, 2021)
Keywords: Evangelische Kirche in Deutschland; Anglikanische Kirche; Meißener Erklärung